Making Space for Social and Emotional Learning in Science Education - Ingram, Erin; Reddick, Kristie; Honaker, Jessica M.; Pearson, Gwen A. (Frontiers in Education, 2021)
Social-emotional learning (SEL) is known to improve student outcomes but is rarely combined with STEM. In this paper we present an action research study to examine the impact of a STEM + SEL curriculum intervention to address a real-world school conflict. One hundred sixth–eighth graders and four teachers participated in an in-person facilitation of a SEL Arthropod curriculum, DIFFERENT. After the intervention, students completed open-ended couplet statements about arthropod behavior, tarantulas, and humans designed to measure sentiment change. Answers were manually coded using inductive coding on a scale of negative (1) to positive (5). Statement sentiments significantly shifted from negative to neutral and negative to positive for all three questions. Neutral to positive shifts were only significant for the couplet statements about arthropod behavior. This study reports the first confirmed instance of successful use of arthropods for SEL within a curriculum that integrates students’ social-emotional skills within a science classroom.